¿Narcoinfierno O Narcolandia? Una Epistemología Intempestiva Sobre El Relato Oficial De La Violencia En México - Christiansen, María L. (European Scientific Journal, ESJ, 2016)
The approach to narcotraffic violence is open to endless explanations, depending on the viewer’s perspective. This article introduces a set of ecological metaphors, whose main advantage is to catch sight of the complexities inherent in the link between the narco-world and the legal culture. In clear opposition to the official story and media about this illicit activity, this paper presents arguments that call into question the presentation style that is common in political discourse and massive journalism. By appealing to notions like "narco-habitat", "relational ecosystem", and "narcoecology", the possibility of understanding the phenomenon of drug trafficking without adopting a position will be explored. On the other hand, it is intended to show that the typical way of conceptualizing this phenomenon (narco-violence) suffers from epistemological biases that close creative interpretations and refreshed meanings. For that reason, the kind of linear, individual, essentialist, condemnatory and criminalist points of view (instituted and naturalized in Mexican public opinion) will berejected.